BALI CATTLE OOCYTE MATURATION RATE ON TCM 199 MEDIA WITH THE ADDITION OF HYPOTAURINE - Novitasari, Ester; Pemayun, Tjok Gde Oka; Suatha, I Ketut; Trilaksana, I Gusti Ngurah Bagus (Buletin Veteriner Udayana, 2022)
Oocyte maturation is an important step in the implementation of in vitro fertilization for embryo transfer. Oocytes collected by aspiration and slicing in general have not yet reached the MII phase needed for in vitro fertilization so oocyte maturation is necessary. The purpose of this study was to determine the maturation level of bali cattle oocytes on TCM 199 medium with the addition of hypotaurine. Oocytes were derived from ovaries obtained from the Pesanggaran Denpasar abattoir and collected using the slicing method. This study used a completely randomized design consisting of 3 groups, namely group I / control (P0: maturation medium without hypotaurine), group II (P1: maturation medium with the addition of 2 mMol hypotaurine), and group III (P2: maturation medium with the addition of 4 mMol hypotaurine). Each group consisted of 27 replications. Oocyte maturation was carried out by 38.5 °C incubation, for 24 hours, with a pressure of CO 2 of 5 %. The results showed that the cumulus cells expansion rate up to cumulus-oocyte complexes (COCs) stages in the P1 group were not significantly different than the P0 group (p> 0.05), but the P2 group showed a significant difference (p <0.05). In term of nuclear maturity, the addition of hypotaurine did not cause a significant difference (p> 0.05) at the GVBD level; but the MI level of the P0 was significantly different from that ofP1 and P2 groups(p <0.05); while at the MII level, there was no significant difference between P0 and P1 (p> 0.05), and that P0 was significantly different to P2 (p <0.05). Collectively, it can be concluded that the addition of 4 mMol hypotaurine to TCM 199 oocyte maturation media increases the rate of expansion of cumulus cells reaching COCs and increase the level of nuclear maturity reaching the MII phase.